Research on second language processing and processing instruction : studies in honor of Bill VanPatten - Leeser, Michael J; Keating, Gregory D.; Wong, Wynne; VanPatten, Bill (Studies in Bilingualism, 2021)
This volume consists of a well-integrated collection of original research articles and theoretical/overview papers on second language (L2) input processing. The primary contributors are former students of Bill VanPatten from the past three decades, and the collection of articles is intended as a tribute to his career and contribution of bringing processing issues to the center stage of research in second language acquisition (SLA) and instructed SLA. The research and theorizing presented in this volume are the most recent in the field and represent innovations in approaches to L2 processing research, including the use of online methodologies (self-paced reading and eye tracking) in the experimental papers. In addition, the editors are recognized authors and researchers who have published on sentence processing, input processing, and processing instruction, and all three editors are either on editorial boards or are associate editors of major L2 journals.